On the origins of marine‐derived freshwater fishes in South America. (15th February 2017) - Bloom, Devin D.; Lovejoy, Nathan R.
Abstract: Aim: The South American fish fauna is renowned for its extraordinary diversity. The majority of this diversity is restricted to few major clades that have ancient associations to freshwater habitats. However, at a higher taxonomic level, the South American ichthyofauna is enriched by an extraordinary number of marine derived lineages – lineages that are endemic to freshwaters, but derived from marine ancestors. Here, we test palaeogeographical hypotheses that attempt to explain the origins and exceptional diversity of marine derived fishes in rivers of South America. Location: South America. Methods: We analysed time‐calibrated molecular phylogenies, ancestral reconstructions and biogeographical patterns for multiple independent marine‐derived lineages. Results: Five of the ten marine‐derived lineages in our analysis have biogeographical patterns and stem ages consistent with invasion from the Atlantic Ocean during the Oligocene or Eocene. Drums and pufferfishes reveal patterns and ages that were consistent with the Miocene marine incursion hypothesis. The Amazonian halfbeak is the only lineage younger than the Miocene and invaded Amazonian freshwaters less than a million years ago. Main Conclusion: Our results suggest Miocene marine incursions and the Pebas Mega‐Wetland may not explain the high diversity of marine derived lineages in South America. Instead, the Pebas Mega‐Wetland may have created a fertile opportunity for diversification of some, but not all marine‐derived lineages.